Saharan dust and the association between particulate matter and daily hospitalisations in Rome, Italy. Issue 6 (15th March 2013) - Alessandrini, Ester Rita; Stafoggia, Massimo; Faustini, Annunziata; Gobbi, Gian Paolo; Forastiere, Francesco
Abstract : Introduction: Outbreaks of Saharan dust have been shown to exacerbate the effect of particulate matter (PM) on mortality. Their role on PM–morbidity association is less clear. This study aims to evaluate the effect of Saharan dust on the PM–hospitalisations association in Rome, Italy. Methods: We studied residents hospitalised in Rome between 2001 and 2004 and performed a time-series analysis to explore the effects of PM2.5, PM2.5–10 and PM10 on cardiac, cerebrovascular and respiratory emergency hospitalisations, respectively. Saharan dust days were identified by combining Light Detection and Ranging observations and analyses from operational models. We tested a dust–PM interaction to evaluate the hypothesis that the PM effect on hospitalisations would be enhanced on dust days. Results: We studied 77 354, 26 557 and 31 620 hospitalisations for cardiac, cerebrovascular and respiratory diseases, respectively, providing effect estimates per IQR. PM2.5–10 was associated with cardiac diseases (3.93%; 95% CI 1.58 to 6.34). PM10 was associated with cardiac (3.37%; 95% CI 1.11 to 5.68), cerebrovascular (2.64%; 95% CI 0.06 to 5.29) and respiratory diseases (3.59%: 95% CI 0.18 to 7.12). No effect of PM2.5 was detected. Saharan dust modified the effect of the PM2.5–10 on respiratory hospitalisations, higher during dust days compared with dust-free days (14.63% vs −0.32%; p value of interaction=0.006). Saharan dust also increased the effect of PM10 on cerebrovascular diseases (5.04% vs 0.90%, p value of interaction=0.143). Discussion: A clear enhanced effect of PM2.5–10 on respiratory diseases and of PM10 on cerebrovascular diseases emerged during Saharan dust outbreaks.